The fi rst report of myeloma with IgD κ and free κ in Indonesia (Medical Journal of Indonesia, 2011)
IgD κ myeloma is a rare plasma cell neoplasm case and has never been reported before in Indonesia. In normal condition, IgD level in blood is very low, therefore increase of IgD level in myeloma could be missed by serum protein electrophoresis.A case of a 59 years old female with severe bone pain is reported. In radiology evaluation, there were thoracal compression fracture and thoracal foramen narrowing. For this patient, the myeloma diagnosis was based on WHO criteria, the stage IIIb was based on Durie and Salmon criteria, and bad prognosis with prognostic index stage III diagnosis was based on International Prognostic Index from International Myeloma Working Group, respectively. In serum protein electrophoresis we found a very small monoclonal spike and in immunofi xation there were monoclonal IgD κ and free light chain κ. (Med J Indones 2011; 20:217-21)